La production mondiale de riz est prévue à la baisse - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Le rapport USDA Rice Outlook 2003/04, paru en août, prévoit ...